Characteristics of GPS TEC variations in the polar cap ionosphere. Issue 5 (14th May 2016) - Watson, Chris; Jayachandran, P. T.; MacDougall, John W.
Abstract: This paper presents statistical characteristics (occurrence rate, amplitude, and frequency) of low‐frequency (<100 mHz) variations in total electron content (TEC) observed in the polar cap ionosphere. TEC variations were primarily associated with mesoscale (tens to hundreds of kilometers) ionization structures and were observed by five Global Positioning System (GPS) receivers over a 6 year period (2009–2014). The altitude of ionization structures was estimated by using colocated ionosonde radars. High data rate receivers combined with broad spatial coverage of multisatellite TEC measurements provided high‐resolution magnetic local time/latitude maps of TEC variation characteristics, which were examined as a function of solar cycle and season. These high‐resolution maps improve upon the current observational picture of mesoscale structuring in the polar cap and provide accurate links to particular magnetospheric source regions. Occurrence of TEC variations was consistently highest in dayside regions mapping to low latitude and plasma mantle boundary layers, while largest‐amplitude TEC variations were observed in dayside regions close to the polar cusp, and lower latitudes around midnight. Occurrence and amplitude of TEC variations increased significantly during the ascending phase of the solar cycle, independent of solar wind conditions, while seasonal statistics showed highest dayside occurrence and amplitude in winter months, lowest in summer, and highest nightside occurrence and amplitude around equinox. A surprising result in the frequency distributions of TEC variations was discrete frequencies of about 2 and 4 mHz, which appeared to originate from regions corresponding to the plasma mantle, immediately poleward of the polar cusp. Key Points: GPS TEC measurements provide a detailed statistical picture of mesoscale ionospheric structuring in the polar cap Occurrence rate and amplitude of TEC variations depend on magnetic coordinates, solar cycle, and season TEC variations at preferential frequencies were observed in regions poleward of the dayside cusp